Acoustic ejection mass spectrometry: An integrated pipeline for ultra-high throughput screening, reactivity profiling, and potency analysis of covalent BTK inhibitors - Ronghai Cheng; Adil Muneer; Maria Hercher; Bekim Bajrami; Reza Nemati (SLAS Technology)
Covalent drug discovery has garnered renewed interest due to its potential to target proteins previously considered ''undruggable.'' Intact protein mass spectrometry (MS) is a critical technique for providing direct evidence of covalent drug modifications to protein targets. However, its application for screening covalent libraries has been hindered by low assay throughput, complex sample preparation, and high protein consumption associated with traditional liquid chromatography-MS (LC-MS) or solid-phase extraction-MS (SPE-MS) platforms. The recent integration of acoustic ejection (AE) with electrospray ionization (ESI) source of high-resolution time-of-flight (TOF) mass spectrometers—specifically, the SCIEX Echo® MS+ with the ZenoTOF 7600—has enabled the direct introduction of intact proteins without desalting at nanoliter volumes from 384 or 1536 well plates into the electrospray ionization (ESI) source of the mass spectrometer, achieving analysis rates of 1–2 seconds per sample. This advancement offers significant potential for covalent library screening and kinetic studies of identified hits due to ultrafast sample introduction and minimal sample consumption. To fully automate this pipeline, the SCIEX Echo® MS+ with ZenoTOF 7600 mass spectrometer was integrated with our internal automation system (HighRes Biosolutions) and the data analysis workflow was automated. Using Bruton’s tyrosine kinase (BTK) as a model, we demonstrated that this integrated pipeline could accelerate covalent drug discovery through covalent library screens, off-target reactivity assessment via GSH reactivity assays, and potency evaluation through kinact/Ki measurements.